Prosper Menière: the man who located vertigo in the inner ear - Péricles MARANHÃO-FILHO; Eliana Teixeira MARANHÃO; Carolina Marques de OLIVEIRA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Since the Greek Aellus Galenum (129 AD - c.200/c.216), vertigo was considered a problem attributed to a cerebral disorder, diagnosed as the manifestation of apoplectiform cerebral congestion. In the mid-19th century, the Frenchman Prosper Menière changed this concept by placing the origin of this symptom in the inner ear. The main objective of this historical note is to highlight who Menière was, his work, and some aspects of the disease that bears his name.